Comparison of the Immunogenicity and Safety of Two Pediatric TBE Vaccines Based on the Far Eastern and European Virus Subtypes. (24th December 2019) - Vorovitch, Mikhail F.; Maikova, Galina B.; Chernokhaeva, Liubov L.; Romanenko, Victor V.; Karganova, Galina G.; Ishmukhametov, Aydar A.
Abstract : Up to 10, 000 cases of tick-borne encephalitis are registered annually, 20% of which occur in children under 17 years of age. A comparison of the immunogenicity and safety between a new pediatric Tick-E-Vac vaccine based on the TBEV strain Sofjin and FSME-IMMUN Junior vaccine was performed in the Sverdlovsk region. The vaccine strains differ from strains of the Siberian subtype of TBEV that dominates in the region. The study was performed on 163 children aged 1 to 15, who received one of the vaccines according to either a conventional or rapid vaccination schedule. Immunogenicity was assessed based on the seroprotection rates and titers of virus-neutralizing antibodies. There were no significant differences in either the immunogenicity or reactogenicity of the pediatric vaccines based on strains of the Far Eastern or European subtypes of TBEV. Under both vaccination schedules, 30 days after the second injection, seroprotection rates were 100% for Tick-E-Vac and greater than 95% for FSME-IMMUN Junior, while the geometric mean titer of TBEV-neutralizing antibodies was at least 2, 4 log10 (1 : 250) for either vaccine. Fourteen days after the second injection according to the rapid schedule, seroprotection rates were significantly lower, ranging from 50% to 63% regardless of the vaccine used. The observed adverse reactions were mild or moderate for both vaccines under both vaccination schedules, with total adverse event rates of less than 25%. Reactogenicity was not associated with the gender or age of the recipients. There were no statistically significant differences in the incidence of adverse reactions between the group of subjects who were baseline seronegative or seropositive. However, 14 days after the second vaccine injection according to the rapid schedule, a statistically significant difference in nAbs titers was identified between groups of children with and without reported reactions.